Vera. Set 4 [videorecording (DVD)] - Cleeves, Ann (distributed by RLJ Entertainment, 2014)
Northumberland Detective Chief Inspector Vera Stanhope and her partner, Detective Sergeant Joe Ashworth, work to unravel four new crimes.